The Effect of Discount and Scarcity Message towards Impulse Buying (A Study on Rosé All Day Cosmetics’ Shopee Live) - Firda Deviyana Rizki; Dian Fordian (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Technological advancements have undeniably transformed consumer shopping behavior. Presently, numerous e-commerce platforms are fervently emphasizing the live shopping feature, including Shopee. Rosé All Day Cosmetics stands as a local cosmetic brand that has successfully increased its sales through Shopee Live. However, the beauty industry remains fiercely competitive. Therefore, Rosé All Day Cosmetics needs to implement appropriate strategies to enhance its sales through Shopee Live. This research aims to investigate the influence of discounts and scarcity messages on consumer impulse buying for Rosé All Day Cosmetics during Shopee Live sessions. The research objects are discounts and scarcity messages as independent variables, while impulse buying serves as the dependent variable. This study employs a descriptive-verification analysis with a survey research design. Non-probability sampling techniques were utilized to select a total of 130 respondents who meet the criteria of being Rosé All Day Cosmetics consumers that have made purchases during Shopee Live events. Multiple linear regression analysis was applied in this research. The research findings reveal a significant impact of both discounts and scarcity messages on impulse buying, both concurrently and individually.